2016
DOI: 10.1371/journal.pone.0159428
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Absorption of Catechins after Intraruminal or Intraduodenal Application of a Green Tea Extract in Cows

Abstract: Green tea catechins have various potential health benefits in humans including anti-inflammatory, anti-oxidative and hepato-protective effects. If present in the circulation, they might have similar effects in ruminants, which are exposed to oxidative stress and fatty liver disease such as dairy cows during the periparturient phase. However, the bioavailability of a substance is a prerequisite for any post absorptive effect in vivo. This study aimed to investigate the appearance of catechins from a green tea e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 50 publications
1
17
0
Order By: Relevance
“…An increase in stability of anthocyanin after copigmentation could be explained by an alteration of its structure. The structure of catechin composes of two benzene rings (called the A-and B-rings) and a dihydropyran heterocycle (the C-ring) with a hydroxyl group on carbon 3 [12]. Catechin has a similar structure to anthocyanin molecule and it is the building blocks of pro-anthocyanidins.…”
Section: = -Kt + C0mentioning
confidence: 99%
“…An increase in stability of anthocyanin after copigmentation could be explained by an alteration of its structure. The structure of catechin composes of two benzene rings (called the A-and B-rings) and a dihydropyran heterocycle (the C-ring) with a hydroxyl group on carbon 3 [12]. Catechin has a similar structure to anthocyanin molecule and it is the building blocks of pro-anthocyanidins.…”
Section: = -Kt + C0mentioning
confidence: 99%
“…The concentrations of major catechins were determined in the plasma by HPLC and the study revealed that intraruminal or orally administered catechins were metabolized by rumen micro-organism, and hence did not appear in blood plasma. Contrary to this, intraduodenal administration resulted in increased concentration of catechins in the plasma (Wein et al, 2016). Green tea waste which is obtained after tea production can be utilized for silage production.…”
Section: Dairymentioning
confidence: 86%
“…In addition, cows fed with supplemented feed showed a reduction in haptoglobin mRNA level (Winkler et al, 2015). Contrary to this, intraduodenal administration resulted in increased concentration of catechins in the plasma (Wein et al, 2016). Green tea extract (GTE) was added (0.028% of dry matter) to the feed of lactating Holstein/Holstein-Gir dairy cows; however, the diet did not alter the milk yield or most of the milk characteristics but reduced the emission of methane gas.…”
Section: Dairymentioning
confidence: 99%
“…The efficiency of microbial metabolism on catechins was well reported in a GTE study on cows [64]. Different doses of GTE was applied intraruminally (10 and 50 mg/kg) and duodenally (10, 20 and 30 mg/kg BW) to dairy cows.…”
Section: Microbial Metabolismmentioning
confidence: 87%